Estimation of Storage Tank Capacities for Different Roof Catchment Areas for Rainwater Harvesting in Dodoma Urban, Tanzania - Mdee, Ombeni J.; Tembo, Malugu M.; Mwegoha, William J. S. (Tanzania Journal of Engineering and Technology, 2022)
This study uses a mass balance model and economic analysis technique to present an estimation of roofing areas and storage tank capacity for Rainwater Harvesting (RWH) system. The water-saved benefits were estimated using the monthly rainfall of over 39 years from 1981 to 2020 and five roofing areas. The proposed roof-storage-ratio method presents the minimum requirement of roof area and storage tank size when the ratio value is closer to 1. The benefit-cost ratio and percentage of reliability indicated the optimal roofing areas ranging between 200 and 300 m2 for storage tank capacity between 20 and 25 m3, with a minimum discount rate of 5%. The increased capacity of storage tank and roofing area would also be a potential factor to increase the investment cost for installing the RWH system. Keywords: Rainwater harvesting, roofing areas, storage tank, economic analysis